Epidemiological aspects mortality of acquired immunodeficiency syndrome in the city of Florianópolis, Brazil (1986–2006) - Bastiani, Janelice; Padilha, Maria Itayra (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The acquired immunodeficiency syndrome (AIDS) affects young adults of working age and commits sectors of society. Objective: To describe epidemiological aspects of AIDS deaths, people aged 13 and older living in Florianópolis (SC) from 1986 to 2006. Methods: descriptive, retrospective study of secondary data from the National Information System for Notifiable Diseases (Sinan), Information System (SIM) and the Brazilian Institute of Statistics and Geography and Statistics (IBGE). Results: There were 1,285 deaths, with 954 men and 331 women. Among them: men aged between 20 and 39, ignored skin color, complete high school and exposure categories for drugs and/or heterosexuality; women aged between 20 and 39, complete high school, ignored skin color, exposure categories and heterosexual heterosexual/drugs. Conclusion: The main epidemiological characteristics were age between 20-39 years old, male, skin color ignored, the average level of schooling. In males, the exposure category, emphasis is given to drugs, heterosexual/drugs, heterosexual and homosexual, the female standouts are the categories heterosexual, heterosexual/drugs and drugs. The ratio of deaths was higher among men than among women. Deaths due to AIDS in Florianópolis, show a decline from 1996 with improved survival for patients with AIDS.